Molecular Targeted Radiosensitizers Opportunities and Challenges - Willers, Henning; Eke, Iris.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana, 2020)
Molecular Targeted Radiosensitizers: Opportunities and Challenges provides the reader with a comprehensive review of key pre-clinical research components required to identify effective radiosensitizing drugs. The book features discussions on the mechanisms and markers of clinical radioresistance, pre-clinical screening of targeted radiosensitizers, 3D radiation biology for studying radiosensitizers, in vivo determinations of local tumor control, genetically engineered mouse models for studying radiosensitizers, targeting the DNA damage response for radiosensitization, targeting tumor metabolism to overcome radioresistance, radiosensitizers in the era of immuno-oncology, and more. Additionally, the book features discussions on high-throughput drug screening, predictive biomarkers, pre-clinical tumor models, and the influence of the tumor microenvironment and the immune system, with a specific focus on the challenges radiation oncologists and medical oncologists currently face in testing radiosensitizers in human cancers. Edited by two acclaimed experts in radiation biology and radiosensitizers, with thirteen chapters contributed by experts, this new volume presents an in-depth look at current developments within a rapidly moving field, with a look at where the field will be heading and providing comprehensive insight into the framework of targeted radiosensitzer development. Essential reading for investigators in cancer research and radiation biology.
Introduction to Molecular Targeted Radiosensitizers: Opportunities and Challenges -- Translating Targeted Radiosensitizers into the Clinic -- Cartography of the Radiogenome of Human Cancers -- Mechanisms and Markers of Clinical Radioresistance -- Preclinical Strategies for Testing of Targeted Radiosensitizers -- 3D Radiation Biology for Identifying Radiosensitizers -- Preclinical in vivo evaluation of novel radiosensitizers by local tumor control experiments -- Genetically Engineered Mouse Models for Studying Radiation Biology and Radiosensitizers -- Targeting the DNA Damage Response for Radiosensitization -- Targeting Tumor Metabolism to Overcome Radioresistance.-Targeting Tumor Hypoxia -- Normalizing the Tumor Microenvironment for Radiosensitization -- Radiosensitizers in the Era of Immuno-Oncology -- Index.
Keywords: Cancer research; Radiotherapy; Pharmacology; Cancer Research; Radiotherapy; Pharmacology/Toxicology.